INFLUENCE OF PULSE FREQUENCY ON THE MINIMUM FLUIDIZATION VELOCITY IN A PULSATING BED - Cala Aiello, Ramon; Riera García, Mislaidys Riera García (Revista Ciências Exatas, 2015)
A pulsating fluidized bed of zeolite and rice husk was studied; were experimentally determined the minimum fluidization velocities and the influence of pulsating conditions, in the gas dynamic characteristics of the fluidized bed. The experimental study included three different beds of zeolite and one of rice husk, varying the pulse frequency in a range from 0 to 140 pulses per minute, in each bed. Is proposes a factorial experiment of two factors, diameter and pulse rate, taking six levels for frequency and three for the diameter. It was determined the equation to predict the minimum fluidization velocity for pulsating fluidized bed. The empirical equation obtained for the zeolites beds, was applied to the rice husk bed, with good results for prediction of the minimum fluidization velocity.